Understanding the genomic information of mycobacterium tuberculosis causing whole genome sequencing approach / Nur Azwin Ismail - Ismail, Nur Azwin (2015)
Mycobacterium tuberculosis (MTB) causes serious disease of tuberculosis which threatens the world with 8 million individuals infected and 2 million deaths reported each year. MTB spreads by aerosol and infects the host through the lungs. This bacillus is phagocytised by macrophages in the lungs and replicate inside these cells. It invades through the macrophage by inhibiting the fusion between phagosome and bactericidal lysosome. The primary macrophage infection results in a proinflammatory response followed by recruitment of other cells that are essentials for the innate and adaptive immune systems. It is known that MTB most commonly affects the lungs. However, it has emerged as an extrapulmonary pathogen that infects any organ system inside the human body. The bacterium is capable of infecting other organ system due to dissemination via lympho-haematogenous route in the early period of the pulmonary infection. A few tuberculosis cases were reported to occur at extrapulmonary sites especially among the immunocomprised. Despite the increase in extrapulmonary TB cases, the mechanisms by which the bacterium subvert host defense mechanism and invade deeper tissue of extrapulmonary site are still poorly understood. Compounding to this lack of knowledge, we therefore use whole genome sequencing platform to complete the genome sequence of extrapulmonary TB strain PR05. With the combination of genomics and bioinformatics analysis, study on the genes essential for virulence and pathogenesis of complete genome sequence of extrapulmonary TB strain PR05 was performed. Based on the annotation of the DNA sequence, proteins function, cellular localization and molecular features were predicted. All the identified genes that are essential for virulence and pathogenesis were grouped into eight categories. Few genes were identified to play role in invasion, and adhesion of extrapulmonary dissemination: erp, fbp, mce and hbhA. Two members (ESX-1 and ESX-5) of MTB unique secretion system, type seven secretion systems (T7SS) was found to be involved in the virulence of M. tuberculosis which affects cell to cell migration of this pathogenic mycobacterium. En route in looking for variations, a comparative analysis between extrapulmonary TB strain and five Pulmonary TB strain was performed to identify the similarities and differences between these strains. The comparative analysis and multiple genome alignment have identified few inversion rearrangement and eleven insertion region encoding 31 genes that play roles in pathogenicity and virulence of MTB. However, current project was not able to pinpoint the exact mechanism causing tropism. Further investigate on the functional importance of genetic variation identified in the extrapulmonary TB strain PR05 is required for better understanding in the mechanism of tropism for extrapulmonary tuberculosis.